Differential effect of mild therapeutic hypothermia depending on the findings of hypoxic encephalopathy on early CT images in patients with post-cardiac arrest syndrome. (July 2018) - Nishikimi, Mitsuaki; Ogura, Takayuki; Nishida, Kazuki; Takahashi, Kunihiko; Fukaya, Kenji; Liu, Keibun; Nakamura, Mitsunobu; Matsui, Shigeyuki; Matsuda, Naoyuki
Abstract: Introduction: The aim of this study was to evaluate the differential effects of mild therapeutic hypothermia (MTH) in post-cardiac arrest syndrome (PCAS) patients depending on the presence/absence of hypoxic encephalopathy (HE) in the early brain CT images obtained before the initiation of MTH. Methods: We conducted a retrospective review of the data of a total of 129 patients with PCAS who were treated by MTH (34 °C) or normothermia treatment (NT) (35 °C or 36 °C), and had undergone brain CT examination prior to the initiation of these treatments. We divided the subjects into 4 groups, namely, the HE(−)/MTH, HE(−)/NT, HE(+)/MTH, and HE(+)/NT groups, for evaluating the interaction effect between the two variables. Then, we compared the neurological outcomes between the HE(−)/MTH and HE(−)/NT groups by multivariate logistic analysis. Good outcome was defined as a Cerebral Performance Category score of ≤2 at 30 days. Results: The percentages of subjects with a good outcome in the HE(−)/MTH and HE(−)/NT group were 68.9% (42/61) and 36.1% (13/36), respectively (p = .003), while those in the HE(+)/MTH and HE(+)/NT groups were lower, at 7.4% (2/27) and 20.0% (1/5), respectively (p = .410), suggesting a statistically significant interaction effect between the two variables (pinteraction = 0.002). In the HE(−) group, MTH was associated with a higher odds ratio of a good outcome as compared to NT (OR 6.80, 95% CI 1.19–38.96, p = .031). Conclusions: The effect of MTH in patients with PCAS differed depending on the presence/absence of evidence of HE on the early CT images.